Authors of zoological publications and nomina are signatures, not persons - Dubois, Alain (Zootaxa, 2008)
Vigny (1979a–b) described the mating calls and the larval morphologies of 12 species and subspecies of the frog genus Xenopus Wagler, 1827. Two years later, the abstract of her thesis dealing with this genus was published (Vigny 1981). In the meanwhile and in the subsequent years, Loumont (1981, 1983, 1984, 1992) described the vocal apparatus of the males of this genus, then two new species of the latter, provided data on its distribution, and published a study of the amphibian fauna of São Tomé and Príncipe. Except for those who had the opportunity to meet her or to hear about her, few zoologists will know that all these papers (and others) were written by the same person, named Catherine Vigny before her marriage, and Catherine Loumont after. However, the fact that this is the same person has no bearing on the references of the papers and on the possibility to find them in a database, a library, the tables of contents of the journals, etc., where they appear under the name by which they were signed: the first ones under Vigny, the second ones under Loumont.